Optimum insulation thickness for the sandwich structure livestock buildings external envelopes in different climate regions of China - Wang, Yang; Li, Baoming; Zheng, Weichao (International Journal of Agricultural and Biological Engineering, 2020)
Determining the optimum insulation thicknesses of external envelopes for livestock buildings are one of the most effective metrics to decrease energy requirements. This study was carried out to determine the optimum insulation thicknesses for livestock buildings in different climate zones, to examine the effects of insulation thickness and material (foam glass, mineral wool, expanded polystyrene, foamed polyurethane, foamed polyvinyl chloride, and expanded polyethylene) on life cycle total cost, life cycle savings, and payback period. The finishing pig houses and laying hen buildings with sandwich wall structures (color steel laminboard) in five typical cities were studied using the degree-days method with economic models. Optimal insulation thicknesses ranged from 0.05 m to 0.25 m and 0.02 m to 0.24 m in finishing pig houses and poultry buildings, respectively; the life cycle total costs ranged from 16.49 to 37.98 /m2 and 13.37 to 36.84 /m2; the life cycle savings ranged from 29.13 to 220.60 /m2 and 0 to 202.13 /m2; and the payback period ranged from 1.11 to 5.81 years and 1.19 to 20.76 years, respectively. Foamed polyurethane provided the highest life cycle savings, while foam glass had the lowest. In this research, the insulation thicknesses for the sandwich structure livestock buildings external envelopes are optimized, and the energy saving can be obtained by using proper insulation thickness in different regions. Furthermore, it can increase the knowledge about energy consumption in the livestock buildings and the results can be also a useful tool for farmers. Keywords: livestock building, insulation material, optimum insulation thicknesses, degree-days, life cycle total cost, life cycle saving, payback period DOI: 10.25165/j.ijabe.20201301.5280 Citation: Wang Y, Li B M, Zheng W C. Optimum insulation thickness for the sandwich structure livestock buildings external envelopes in different climate regions of China. Int J Agric & Biol Eng, 2020; 13(1): 29–41.